KETAKSAAN SILABUS MATA PELAJARAN BAHASA ARAB TAHUN 2016 UNTUK JENJANG MENENGAH ATAS - Moh. Ainin; Imam Asrori (Arabi : Journal of Arabic Studies, 2019)
The Ministry of National Education has developed the 2016 Arabic language learning syllabus for high school level (SMA and MA) with specialization programs. This syllabus is often complained by Arabic teachers. This study was conducted with a qualitative approach because the data were analyzed in the form of information presented in narrative form and the results of the analysis were also presented in a narrative-qualitative manner. Data were analyzed using the interactive model of Miles and Huberman and strengthened by the Krippendorff model content analysis technique. Based on the results of a study of the contents of the syllabus, it was found that there were substantial ambiguities. This imposedness includes imposed identity and imposed content. The ambiguity was present in the form of imposed identity in the mention of names of subjects (subjects of Arabic language and literature, courses in Arabic, even subjects of Indonesian / French). The ambiguity of content includes: inconsistencies between components, KD formulation, cognitive-psychomotor domains, language skills (receptive-productive, and impersonal meaning.